(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article the features of the development of the novel genre in Kazakh literature of the end of XX – the beginning of XXI centuries are considered. On the basis of specific works’ analysis the author reveals and defines the directions of ideologically artistic searches of writers, tendencies of progress of modern Kazakh prose. The factors which caused transformation of the novel genre are highlighted. Key semantic levels of this genre are established. The peculiarities of constructing Kazakh writers’ works are revealed. The author of the article affirms and proves that novels of the late 20-th century – early 21-st century are characterized by their multi-levelness, dialogism, deep dramatic nature, depth of narration. The prose writers give great attention to the inner world of the person, system of relationships of the person and society. Modernization of the genre of novel is shown at the level of conflict which assumes a more complex and controversial character. It is established that in the modern Kazakh novel the combination of elements of various genres is observed. In the works of writers the elements of psychological, social, philosophical, historical, detective, fantastic, satirical novels quite often interweave which gives versatility to the represented world, enriches the content and structure of works